Factors Influencing Anti-Corruption Disclosure in Indonesia - Graciella, Tamara; Sutardja, Meco; Setiono, Bambang (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
This study aims to determine the factors that influence anti-corruption disclosure by examining the effect of independence of the board of commissioners, government ownership, company size, and media exposure partially on anti-corruption disclosure. The sampling method used was purposive sampling, with a total sample of 38 companies participating in the Asia Sustainability Reporting Rating for the 2018–2020 period that are listed on the Indonesia Stock Exchange. The data used in this study is secondary data, which are available in the annual reports and sustainability reports of the study’s sample. Data collection in this study is done using documentation techniques. This study uses Smart PLS (Partial Least Square) to test the hypothesis. The analytical methods used in this study include the outer loadings test, R Square, and path coefficient significance. The results show that media exposure has a significant positive effect on anti-corruption disclosure, while independence of the board of commissioners, government ownership, and company size have no effect on anti-corruption disclosure.